2022
DOI: 10.1093/nar/gkac362
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of PNA-based antisense antibiotics targeting various essential genes in uropathogenicEscherichia coli

Abstract: Antisense peptide nucleic acids (PNAs) that target mRNAs of essential bacterial genes exhibit specific bactericidal effects in several microbial species, but our mechanistic understanding of PNA activity and their target gene spectrum is limited. Here, we present a systematic analysis of PNAs targeting 11 essential genes with varying expression levels in uropathogenic Escherichia coli (UPEC). We demonstrate that UPEC is susceptible to killing by peptide-conjugated PNAs, especially when targeting the widely-use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 113 publications
6
56
1
Order By: Relevance
“…Recent reports using different E. coli strains showed that PNA-mRNA T m positively correlates with growth inhibition (Goltermann et al 2019) and is associated with in vitro translation inhibition of the target gene (Popella et al 2022). We therefore integrated T m predictions for PNA-RNA duplexes as a feature in MASON (see methods, Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports using different E. coli strains showed that PNA-mRNA T m positively correlates with growth inhibition (Goltermann et al 2019) and is associated with in vitro translation inhibition of the target gene (Popella et al 2022). We therefore integrated T m predictions for PNA-RNA duplexes as a feature in MASON (see methods, Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5B, E). This is likely an underestimate of the total number of effective off-targets, as we have recently shown that targeting of mRNAs by PNAs does not necessarily lead to depletion of the transcript (Popella et al 2022). Low PNA-mRNA affinity appears to ameliorate off-target activity, as we found that requiring a predicted T m of >20 °C increased the fraction of depleted off-targets to 13.6% and 25.1%, respectively (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, this property can also be exploited to discriminate between direct and indirect effects: for example, we show that acpP -PNA directly inhibits translation of acpP , but not of fabF (Figure 5A , B ). In contrast, in vivo the PNA influences the stability of the entire dicistronic acpP - fabF mRNA ( 27 , 28 ), which makes it harder to assess its direct effect on translation.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, since Ribo-seq is performed on living cells, it can be difficult to dissect direct and indirect effects on translation. This is exemplified by antisense antibiotics ( 24–26 ), whose import via carrier peptides broadly affects gene expression in addition to the desired antisense inhibition of the targeted gene of interest ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%